1996
DOI: 10.1259/0007-1285-69-818-114
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioneuroma: computed tomography and magnetic resonance features

Abstract: 12 patients who had histological proven ganglioneuromas were investigated by computed tomography (CT) and magnetic resonance (MR) imaging. CT scans (n = 11), conventional spin-echo MR images (n = 10) and dynamic MR images (n = 5) were acquired. All lesions showed a well defined, oval shape. Five lesions (42%) showed calcification which was punctate in four and coarse in one on CT. CT attenuation was predominantly low in three of 10 (30%) and intermediate in the remaining seven (70%). In all lesions MR signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
83
1
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 24 publications
4
83
1
8
Order By: Relevance
“…In one of our patients, however, calcification was dense and nodular. At enhanced CT, varying degrees of contrast enhancement have been described; Ichikawa et al (10), for example, reported delayed heterogeneous enhancement, and in our case, enhancement was delayed, septum-like and heterogeneous. Variations are explained by the presence in the tumors of an abundance of myxoid matrices, resulting in delayed and progressive accumulation of contrast material in extracellular space.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In one of our patients, however, calcification was dense and nodular. At enhanced CT, varying degrees of contrast enhancement have been described; Ichikawa et al (10), for example, reported delayed heterogeneous enhancement, and in our case, enhancement was delayed, septum-like and heterogeneous. Variations are explained by the presence in the tumors of an abundance of myxoid matrices, resulting in delayed and progressive accumulation of contrast material in extracellular space.…”
Section: Discussionsupporting
confidence: 50%
“…The tumors contain calcification in about 20% of cases (8), a feature which in childhood may help differentiate ganglioneuroma from neuroblastoma (3). In the latter, calcification is more often amorphous and of a rough pattern (3,9), while in ganglioneuromas it is usually discrete and punctate (8,10). In one of our patients, however, calcification was dense and nodular.…”
Section: Discussionmentioning
confidence: 54%
“…Whirlpool sigh is the characteristics feature on T2W1 that means a few curved or linear hypointense signal region exists in surrounding extensive hyperintense signal region [12,13]. Pathologic morphology of ganglioneuroma is constitued by strip Schwann cell and tufted gangliocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Punctate and coarse calcification could also be observed in certain cases in a disseminated sprinkled pattern, and administration of contrast media could lead to low or moderate enhancement. MRI is superior to CT in defining the intraspinal involvement; low intensity on T1-weighted images (T1WI), marked high intensity on T2-weighted images (T2WI) and gradual increasing enhancement on dynamic MR images are typical appearances of GN (19).…”
Section: Discussionmentioning
confidence: 99%